2022
DOI: 10.3389/fonc.2022.924696
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Gut Microbiota to Improve Hepatobiliary Tumor Treatments: Recent Advances

Abstract: Hepatobiliary tumors, which include cholangiocarcinoma, hepatocellular carcinoma (HCC), and gallbladder cancer, are common cancers that have high morbidity and mortality rates and poor survival outcomes. In humans, the microbiota is comprised of symbiotic microbial cells (10-100 trillion) that belong to the bacterial ecosystem mainly residing in the gut. The gut microbiota is a complicated group that can largely be found in the intestine and has a dual role in cancer occurrence and progression. Previous resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 146 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…Probiotics can reduce toxic chemical induced hepatocarcinogenesis by rebuilding intestinal homeostasis and improving intestinal and liver inflammation ( 49 ). Research shows that dysbiosis of intestinal microbiota may be one cause of HCC, and probiotics that restore intestinal microbiota function are an effective and safe strategy to treat HCC ( 50 , 51 ). Fecal microbiota transplantation (FMT) is the transplantation of fecal microbiota suspension from a healthy pre-screened donor to an individual with disease ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics can reduce toxic chemical induced hepatocarcinogenesis by rebuilding intestinal homeostasis and improving intestinal and liver inflammation ( 49 ). Research shows that dysbiosis of intestinal microbiota may be one cause of HCC, and probiotics that restore intestinal microbiota function are an effective and safe strategy to treat HCC ( 50 , 51 ). Fecal microbiota transplantation (FMT) is the transplantation of fecal microbiota suspension from a healthy pre-screened donor to an individual with disease ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCA is the second most common primary liver cancer, accounting for about 15%. Most patients with CCA are diagnosed at an advanced disease stage and have a poor prognosis due to a lack of obvious symptoms to promote early diagnosis [ 24 ]. The gastrointestinal system is one of the largest reservoirs of microorganisms in the human body, and it holds both commensal and pathogenic microbial species [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The F/B ratio has been reported as a potential marker of pathophysiologic conditions [ 44 , 45 ]. The fecal F/B ratio may influence host metabolism and inflammation since it might play a potential anti-inflammatory role [ 46 ], and long-term chronic inflammation is associated with the incidence and development of cancer [ 24 ]. Our study showed that the F/B ratio of the CCA group was significantly lower than that of the HNC group, which is a good way to distinguish a healthy state from a diseased state.…”
Section: Discussionmentioning
confidence: 99%
“…The source of tumor-associated Th17 cells may be also connected to the gut [22]. In addition, Th17 cells seem to be intensely linked with HCC progression, probably via assisting their angiogenesis [20,23]. Interestingly, probiotic alteration of the gut microbiota could help prevent the occurrence of HCC [24].…”
Section: Hcc and Gut Microbiotamentioning
confidence: 99%